Sub-surface current meanders along the Namibian shelf. (January 2021) - Hagen, Eberhard; Feistel, Rainer
Abstract: The influence of long, sub-inertial waves travelling poleward on spatiotemporal fluctuations in the hydrography of coastal upwelling areas has widely been discussed theoretically in the literature since the late 1970s. In this paper, in contrast, measured unexpected wave-like changes in the intermediate density field along the Namibian continental slope are presented and suggested to be the result of a geostrophically adjusted southward current with significant on-offshore meanders. Hydrographic measurements had been carried out on board of r/v 'METEOR' along the 200-m isobath above the Namibian continental shelf (19–23 °S) during seven days in October/November 2000. Measured water properties rhythmically change in space between oceanic (on-shore meander, well oxygenated, dominant Eastern South Atlantic Central Water, ESACW) and coastal waters (off-shore meander, poorly oxygenated, dominant South Atlantic Central Water, SACW). The first case is accompanied by downward displacements of the permanent pycnocline, while the second one corresponds to the opposite situation. The distance between these rather periodic along-section changes in stratification is roughly constant and estimated to be about 60 km. At two hydrographic station positions, duplicate measurements enable an estimation of the associated southward propagation speed of the signal. The obtained value of about 0.16 m/s roughly peaks at the pressure level of about 70 dbar, and the corresponding time scale is estimated to be a few days. Highlights: New periodic hydrographic structures on the Namibian shelf in the Benguela upwelling zone have been discovered. Observed structures are suggested here to result from a topographically trapped, southward meander current.